2020
DOI: 10.1249/mss.0000000000002269
|View full text |Cite
|
Sign up to set email alerts
|

No Clinical Predictors of Postconcussion Musculoskeletal Injury in College Athletes

Abstract: Purpose This study aimed to identify clinical predictors of postconcussion subsequent musculoskeletal (MSK) injuries. Methods We recruited 66 National Collegiate Athletic Association intercollegiate student-athletes with a diagnosed concussion as well as 36 National Collegiate Athletic Association student-athletes without a concussion. All participants completed a multifaceted concussion baseline consisting of 1) 22-item 0–6 self-reported symptom checkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“… 35 , 42 Overall, it appears the elevated risk for LE injury post-SRC is present in both short and long terms after an athlete returns to unrestricted participation. 4 , 5 , 12 , 14 , 29 Compared with previous decades, it appears that SRCs are increasing within the collegiate athlete population, 9 which may predispose more competitors to subsequent LE injuries.…”
mentioning
confidence: 99%
“… 35 , 42 Overall, it appears the elevated risk for LE injury post-SRC is present in both short and long terms after an athlete returns to unrestricted participation. 4 , 5 , 12 , 14 , 29 Compared with previous decades, it appears that SRCs are increasing within the collegiate athlete population, 9 which may predispose more competitors to subsequent LE injuries.…”
mentioning
confidence: 99%
“…10,17 However, the exact neuromuscular mechanism is still unknown. 6 This is an area of conflicting evidence, as some have postulated that injury risk after an SRC is an artifact of an athlete having an overall increased risk of injury regardless of the concussion event. 7,24,34 These authors hypothesized that the increased risk of injury before and after an SRC may be due to ''risk-taking behavior'' or play style.…”
Section: Injury Risk Interpretationmentioning
confidence: 99%
“…4 Furthermore, the use of inertial sensor technology may help address some of the limitations of the traditional clinical assessments which have shown no utility in identifying those at an increased risk of musculoskeletal injury post-concussion. 34 For example, recent prospective research by Johnston et al 15 reported that Rugby Union players with poorer dynamic balance performance measured using inertial sensor technology during the YBT were at a three times greater relative-risk of concussion than individuals with optimal performance. Additionally, individuals with impaired dynamic balance performance have been shown to possess an increased risk of sustaining lower limb injuries such as lateral ankle sprains 35 and anterior cruciate ligament ruptures.…”
Section: F I G U R E 2 Violin Plots Illustratingmentioning
confidence: 99%